39.8k views
4 votes
30
Solve by elimination:
2x - 3y = -6
-2x - 2y = 26 ,

User Aghd
by
5.0k points

1 Answer

4 votes

Answer:

x=-9,y=-4

Explanation:

2x-3y=-6...(1)

-2x-2y=26...(2)

To solve we will have to eliminate one of the given variables, the variable to be eliminated is x

And it can be done by adding up (1) and (2)

It gives

-5y=20

Divide both sides by-5

y=-4

Then substitute the value of y into (1)

2x-3(-4)=-6

2x+12=-6

Substrate 12 from both sides

2x=-18

Divide both sides by 2

x=-9

Therefore x gives -9 and y gives-4

User LemonMan
by
5.3k points